Effects for Land Deed Official (PPAT) in the Sale and Purchase Agreements of Land Which Does Not Match With Procedure of the Land Deed Making in Magelang - Sahudi Sahudi; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study was to analyze: 1) The forms of the deed of sale of land that is not in accordance with the procedures of the Land Deed Manufacture in Magelang. 2) The cause of the Deed of Sale and Purchase of Land not in accordance with the procedures of the Land Deed Manufacture in Magelang. 3) The legal consequences for the Land Deed Official (PPAT) in the manufacture of a deed of sale of land that is not in accordance with the procedures show a deed of land in Magelang.This research is normative juridical approach, the sociological juridical approach. The collection of primary and secondary data obtained by interview and literature study, then analyzed by qualitative analysis method.The research results are: 1) The forms of the deed of sale of land that is not in accordance with the procedures Making Land Deed in Magelang among which the sales and purchase agreement by the parties do not before PPAT who signed the deed of sale (deposit certificate), signing not done in the same time in front of PPAT, the transaction price values contained in the deed of sale is different from the actual transaction value. 2) The cause of the Deed of Sale and Purchase of Land not in accordance with the procedures Making Land Deed in Magelang, namely the existence of a situation which requires PPAT to manufacture the deed of sale that is not in accordance with the procedures deed PPAT is needed in order to save a sale and purchase transaction , their high trust between the parties with PPAT, a factor the value of security be so PPAT would follow the wishes of the parties. 3) The legal consequences for Deed Official Land (PPAT) in the manufacture of a deed of sale of land that is not in accordance with the procedures show a deed of land in the district of Magelang is PPAT be dishonorably discharged from his position, may be subject to administrative sanctions and fines in accordance with the regulations applicable.Keywords: Sale and Purchase Agreements; PPAT; Effects.